Traditional bone setting service users and associated factors among people with trauma in Mecha district, Ethiopia - Belaynew Adugna Endeshaw; Worku Belay; Aderaw Gete; Kassawmar Angaw Bogale; Bekalu Wubeshet; Abebaw Gedef Azene; Gizachew Tadesse Wassie; Wubshet Aderaw; Birlew Teshome; Assefa Gebeyehu Muluneh; Berihun Assefa Demissie (BMC, 2023)
Abstract World Health Organization stated that traditional medicine is an important part of health care and countries need to consider integrating it into their primary health care system. Traditional bone setting has a long history in Ethiopia and it enjoys enormous acceptance in the community. However, these methods are raw, there is no standardized training and at the same time, complications are common. Therefore, this research aimed to assess the prevalence of traditional bone setting service utilization and associated factors among people with trauma in Mecha district. Methods A Community- based cross-sectional study design was employed from January 15 to February 15, 2021. A total of 836 participants were selected using a simple random sampling technique. Binary and multiple logistic regressions were employed to assess the association between the independent variables with traditional bone setting service utilization. Results The prevalence of traditional bone setting service utilization was 46.05%. Factors significantly associated with TBS utilization were: Age ≥ 60 years (AOR = 0.13, 95% CI: 0.03- 0.43), rural residence (AOR = 3.63, 95% CI: 1.76 -7.50), occupation (merchant (AOR = 0.21, 95% CI: 0.07 -0.61), and housewife (AOR = 4.12, 95% CI: 1.33 -12.70), type of trauma: dislocation (AOR = 6.40, 95% CI: 3.69-11.10), and strain (AOR = 2.09, 95% CI: 1.05- 4.14)), site of trauma: extremity (AOR = 0.20, 95% CI: 0.11, 0.37), trunk (AOR = 0.08, 95% CI: 0.03-0.22), and shoulder (AOR = 0.20, 95% CI: 0.11-0.37), cause of trauma: fall down and natural deformity (AOR = 9.87, 95% CI: 5.93-16.42) and household annual income greater than > 36,500 (AOR = 2.33, 95% CI: 1.29-4.22). Conclusion The prevalence of traditional bone setting practice is high in the study area, despite recent advancements in the practice of orthopedics and trauma in Ethiopia. Since TBS services are more accepted in society, the integration of TBS into the health care delivery system is recommended.